BUAH MENTIMUN DAN TOMAT MENINGKATKAN DERAJAT KEASAMAN (pH) saliva DALAM RONGGA MULUT - Wiworo Haryani; Irma Siregar; Laras Agitya Ratnaningtyas (Jurnal Riset Kesehatan, 2016)
The research aims to know the effects of chewing the fruit of cucumbers and tomatoes to the pH of the saliva. This research is a study of Pre-experiments with One Group Pretest – Posttest Design. Research done on April 2014. Location of research in junior high Country 2 Turi. Population research is grade VII Junior High School Country 2 Turi criteria 12-14 years of age, in good health, there are no dental caries reaches the pulpa, and there are no teeth missing. Influence of variable that is chewing on cucumber fruit and tomato fruit Chews, variable affected the pH of saliva. Processing and analysis of test data using the Paired Sample T-Test. The average pH of saliva before chewing on cucumber fruit is 6.7700 and after chewing on cucumber fruit is 6.8567 0.0867 rises. The average pH of saliva before chewing fruit tomato is 6.7833 and after chewing the fruit of tomato was 7.0067 0.2234 rises. After the analysis is performed using a test for paired sample t-test revealed the influence of meaning between before and after chewing the fruit of cucumbers, p=0.001, and there is a meaningful influence between before and after chewing fruit tomato p=0.000.